Analisis Pelaksanaan Tanggungjawab Sosial Perusahaan (CSR) PT. Toba Pulp Lestari, Tbk di Kabupaten Toba Samosir Ditinjau Dari UU PT. No. 40 Tahun 2007 - Ebenezer Simanullang; Bismar Nasution; Muhammad Yamin; Mahmul Siregar (Universitas Sumatera Utara, 2019)
Abstract. In Indonesia, the implementation of corporate social responsibility (CSR) was regulated in Law Number 40 of 2007 about Limited Company which contained in Chapter V Article 74, the further provision about Social and Environmental Responsibility were regulated with Governments Regulation No. 47 of 2012 in Article 4. The fund which channeled through corporate social responsibility was in the amout of 1% of net sales (Net Sales). The CSR implementation constraint which experienced by PT. Toba Pulp Lestari, Tbk in an internal company manner was in the implementation of social investment (development) program. Likewise, the external constraint which experienced by PT Toba Pulp Lestari, Tbk among others, were the existence of management institution of CD / CSR fund company formed by the Regional Government which previously formed and the result of report after audited